Aluminum oxide nanotubes fabricated via laser ablation process: Application as superhydrophobic surfaces. (November 2022) - Jafari Eskandari, Mohammad; Araghchi, Masoud; Daneshmand, Hamid
Graphical abstract: Aluminum-oxide nanotubes and their applications in superhydrophobic surfaces. Highlights: Aluminum oxide nanotubes were synthesized by laser ablation process. A continuous-wave fiber laser irradiated on an aluminum surface coated with gold nanolayer. These metal-oxide nanotubes had a single crystal structure. Aluminum-oxide nanotubes structures indicated a near superhydrophobic behavior. Abstract: Laser-induced surface structuring is a promising technique for the novel formation of nanostructures that can effectively be used to modify the surface and synthesis of nanostructures. Metallic and semiconductor oxide nanotubes presently have been attracted in an extensive domain of materials that range from optoelectronic, gas sensor, catalyst, and superhydrophobic surface applications. In this work, aluminum oxide nanotubes were successfully fabricated by laser ablation processes of a 40-nm gold nanolayer coated on an aluminum surface plate inside the ethanol. A continuous-wave fiber laser with a power of 40 W was used to create Al2 O3 nanotubes. The electron diffraction pattern analysis of these nanotubes demonstrated that the Al2 O3 nanotubes had a single crystal and hexagonal crystal structure with the lattice parameter of a = 0.432 nm as well as zone axis of z = 1 2 ¯ 1 3 ¯ . These nanotubes had a highly-crystalline structure with about 50–200 nm diameters, 10–50 nm wall thicknesses, and 5–20 µm length as well as open-ended. In addition, aluminum oxide nanotubes structures indicated a near superhydrophobic behavior with about 155° ± 2° as a contact angle using experimental and simulation approaches. Meanwhile, molecular dynamics simulation was applied to investigate the wetting property of the aluminum surface and the aluminum surface containing Al2 O3 nanoparticles and Al2 O3 nanotubes. The effect of the Al2 O3 nanotubes on wetting properties was considerable compared to the Al2 O3 nanoparticles. The growth mechanism of Al2 O3 nanotubes was proposed and illustrated in detail. Also, the obtained findings of this work can be applied to superhydrophobic surfaces in industrial production.